2022
DOI: 10.1007/s41109-022-00457-z
|View full text |Cite
|
Sign up to set email alerts
|

The film festival sector and its networked structures of gender inequality

Abstract: The global film industry is shaped by gender inequality. Women are structurally underrepresented in professional roles that include high levels of creative and economic decision-making power, such as directors, writers, and producers. In our study, we ask to what extent the film festival sector, a prestigious sub-field of the film industry, is structured by gender biases. To address this question, we conceptualize the festival sector as a one-mode network consisting of film festivals that are connected through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…This provides valuable insights into the relationship between ‘quality’ of networks and ‘quality’ of jobs, in examining racialized, gendered effects resulting from networks’ recognition of social capital. Similarly, a recent study of the film festival sector found that gendered network structures explained the scarcer presence of films by women‐only core creative teams, resulting in a skewed degree of distribution of films by men‐only teams and a more pronounced festival hit dynamic (Ehrich et al., 2022; see also Lutter, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…This provides valuable insights into the relationship between ‘quality’ of networks and ‘quality’ of jobs, in examining racialized, gendered effects resulting from networks’ recognition of social capital. Similarly, a recent study of the film festival sector found that gendered network structures explained the scarcer presence of films by women‐only core creative teams, resulting in a skewed degree of distribution of films by men‐only teams and a more pronounced festival hit dynamic (Ehrich et al., 2022; see also Lutter, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Following the preceding discussion, we focus on diversity in film festival programming as a marker of public value. Diversity has been researched in a variety of film industry contexts, including program diversity in television [42], cultural diversity in film [43,44], and gender diversity in film production [45], distribution [46], and festivals [20,47].…”
Section: Film Festival Diversitymentioning
confidence: 99%
“…Network methods have been applied to the broader domain of film, such as to study collaboration between creatives in film production [45,[60][61][62] or facilitate the discovery of films via multi-layer network models [63]. So far, however, the applications of network analysis to film festival data have been limited in either regional scope [64] or the time period of a single year [20].…”
Section: Network Connectedness and Diversitymentioning
confidence: 99%
See 2 more Smart Citations